PENGARUH BRAND IMAGE, SERVICE QUALITY, DAN WORD OF MOUTH TERHADAP REPURCHASE INTENSION PADA PRODUK TOKO FEBSHOP019 (STUDI KASUS PADA SHOPEE INDONESIA) - Putri Febiani Iskandar; Irfan Arif Husen; Desy Amaliati Setiawan; Zulkarnaini, Zulkarnaini (Bajang Institute, 2024)
This research aims to determine and analyze the influence of brand image, service quality and word of mouth on product repurchase intentions at the Febshop019 store in the Shopee application. The population in this study are customers/consumers from the Febshop019 store on the Shopee application. The sampling technique used purposive sampling and those who met the criteria for sampling were 100 respondents. The data used in this research is secondary data in the form of questionnaire results distributed to 100 respondents. Data collection techniques using observation and questionnaires. Researchers used the SPPS version 25 tool in testing the data. Data analysis techniques use descriptive statistical analysis, classical assumption testing, multiple linear analysis and hypothesis testing. The research results show that partially the brand image variable does not have a significant influence on repurchase intention, while the service quality and word of mouth variables have a significant influence on repurchase intention. Simultaneously, the three variables, namely brand image, service quality and word of mouth, together have a significant influence on product repurchase intentions at the Febshop019 store on the Shopee Application